Analysis of Basic Passing Technique Skills in Futsal Games at Palopo 4 Public Middle School - Prasetya, Rezha Chandra; Ahmad, Ahmad; Aliah, Husnani (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
This research is a type of descriptive research. This study aims to determine the Passing Skills in the Futsal Game of SMP Negeri 4 Palopo. This research uses descriptive quantitative research by collecting data based on real data then compiling, processing and analyzing it to get a picture of the existing problems. The population is all Futsal players at SMP Negeri 4 Palopo.All 20 players of the Palopo 4 Public Middle School futsal team were used as samples. The sampling technique uses a saturated sample. The data analysis technique used is descriptive analysis, percentage descriptive analysis. The results of the completeness level of SMP Negeri 4 Palopo students in this study showed the classification of "very good" and "very poor". Then where are the results of the end of the passing skill test for students of SMP Negeri 4 Palopo, as follows: Very Good category 10% (2 students), Good category 35% (7 students), Moderate category 45% (9 students), Less category 5% (1 student), and Very Poor category of 5% (1 student). So based on these data it can be concluded that Passing Futsal skills in Palopo 4 Public Middle School students are in the "moderate" category. Research shows that passing futsal skills for students of SMP Negeri 4 Palopo are in the moderate category.